Mitigating Contemporary Trauma Impacts Using Ancient Applications - Morris, Gavin; Groom, Rachel; Schuberg, Emma; Atkinson, Judy; Atkinson, Caroline; Ungunmerr-Baumann, Miriam-Rose (Frontiers in Psychology, 2022)
The COVID-19 pandemic represents the most significant global challenge in a generation. Based on extant data from previous pandemics, demographic, occupational, and psychological factors have been linked to distress and for some vulnerable members of society. COVID-19 has added to the layers of grief and distress of existing trauma. Evidence-based frameworks exist to guide our individual and collective response to reduce the trauma associated with the experience of a pandemic. Pandemic and post-pandemic measures to ameliorate impacts require a multi-disciplined approach, central to which is community connectedness, resilience, and access to support. We advocate for the acceptance and broader application of Dadirri, a healing practice held by the Ngan’gikurunggurr and Ngen'giwumirri Aboriginal people of the Daly River region in the Northern Territory, Australia. This modality engages therapeutic phases that are comparable with other practiced trauma therapies. The demonstrated therapeutic outcomes from Dadirri can be attained through an individualistic or in a relational engagement context. This practice is accessible to all ages, is nonspecific to gender and is suitable for people constrained in their mobility or limited by resources, pertinent in pandemic affected settings.